2020
DOI: 10.1016/j.annemergmed.2019.08.420
|View full text |Cite
|
Sign up to set email alerts
|

Treating Opioid Withdrawal With Buprenorphine in a Community Hospital Emergency Department: An Outreach Program

Abstract: Study objective: We assess the feasibility of using our community hospital emergency department (ED) as an immediate portal to medication-assisted treatment for patients in opioid withdrawal. Methods: This was a prospective observational cohort study. In collaboration with an outpatient substance abuse treatment center, we alerted the public through media outlets that individuals could receive immediate buprenorphine treatment for opioid withdrawal in the ED, with rapid referral for medication-assisted treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…Our search revealed eight non‐randomised observational studies, mostly performed in the last 2 years (Table 2). These have demonstrated that when buprenorphine is initiated in the ED with a warm handover (direct communication) to outpatient care, there is substantial engagement in formal addiction treatment in the following months 34–40 . In some cases, this was achieved by utilising peer workers, social workers and rapid access bridge clinics; a model that is likely to overcome the extra workload perceived by physicians and prevent loss to follow‐up during this high‐risk period 33,34,39,40 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our search revealed eight non‐randomised observational studies, mostly performed in the last 2 years (Table 2). These have demonstrated that when buprenorphine is initiated in the ED with a warm handover (direct communication) to outpatient care, there is substantial engagement in formal addiction treatment in the following months 34–40 . In some cases, this was achieved by utilising peer workers, social workers and rapid access bridge clinics; a model that is likely to overcome the extra workload perceived by physicians and prevent loss to follow‐up during this high‐risk period 33,34,39,40 …”
Section: Resultsmentioning
confidence: 99%
“…In all studies, the majority of participants presented to their first follow‐up appointment, and at 30 days more than two thirds of participants were retained 35–39 . In one study, 37% of participants were still in active treatment at 6 months 37 .…”
Section: Resultsmentioning
confidence: 99%
“…30 Medication for addiction treatment has been initiated in many EDs, with the typical goal of continuation of the program on an outpatient basis. [31][32][33] These programs have demonstrated better short-term improvement in treatment and illicit opioid use rates over referral only or brief intervention.…”
Section: Medication For Addiction Treatmentmentioning
confidence: 99%
“… 15 Unlike naltrexone, buprenorphine does not require a supervised withdrawal period and can be safely induced either in the emergency department (ED), the primary care setting, or at home. 16 Unlike methadone, buprenorphine can be prescribed by any physician or advanced practice provider after undergoing proper training, and multiple days’ doses can be dispensed at once. 16 These attributes make buprenorphine a favorable form of MAT to be prescribed by emergency physicians, attributes that become more relevant given that the ED is a key point of contact with the healthcare system for many OUD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies, which were conducted at urban, academic medical centers using 30-day enrollment in an MAT program as a primary endpoint, found that significant proportions of subjects attained the desired outcome. 16 , 18 21 In this study we sought to determine whether buprenorphine prescription by emergency care providers in a community hospital decreased healthcare utilization in patients with OUD. We hypothesized that buprenorphine prescription by emergency care providers would safely decrease healthcare utilization for OUD patients compared to matched controls, resulting in decreased rates of ED-visit and hospitalization rates without an increase in opioid overdose rates.…”
Section: Introductionmentioning
confidence: 99%